Investigating the Behavior of Buildings under the Effect of the New Design Ground Motion of Iraq - Mustafa Shakir Farman; AbdulMuttalib Isa Said (Salehan Institute of Higher Education, 2019)
Recently, Iraq has experienced an increase in seismic activity, especially, near the east boundary with Iran which enhanced the need to study its effect on the behavior of buildings. In this study, a comprehensive methodology was applied to investigate the behavior of a moment frame system with respect to its height after subjected to the design ground motion at Baghdad according to the recently developed seismic hazard maps and, after developing and designing the required configurations of archetype models, specifying life safety as an aimed performance level, modeling nonlinearity and applying the nonlinear static analysis (NSP) according to ASCE/SEI41-13, FEMA356 and FEMA P-695. This methodology is started by sizing members cross-sectional dimensions and applying reinforcement detailing requirements according to ACI318-14. Results show that, for a given building height and number of bays, inelastic drifts increase with decreasing the bay width because the overall building stiffness is decreased and it will be more slender, and consequently, the P- delta effects increased. Also, as the building height increased, both, target and minimum shear capacities decrease and the target displacement increases under the effect of the same earthquake ground motion. Consequently, a necessary limitation on the height of these buildings were deduced to ensure their ability to withstand the future ground shaking and, in the same time, maintaining the life safety performance level of damage. Where, it is found that the maximum allowed heights of framed buildings in Baghdad are 17, 25 and 32 stories for 6, 7.5 and 9 m bay widths, respectively.